Use the properties of operations and rules for multiplying and dividing to solve:

(−2)×(15)÷(23)×(−56)÷(34)

5 answers

To solve the expression (−2)×(15)÷(23)×(−56)÷(34), we can follow the order of operations (also known as PEMDAS):

Step 1: Multiply -2 and 15
-2 × 15 = -30

Step 2: Divide -30 by 23
-30 ÷ 23 ≈ -1.3043478260869565

Step 3: Multiply -1.3043478260869565 by -56
-1.3043478260869565 × -56 ≈ 73.04347826086956

Step 4: Divide 73.04347826086956 by 34
73.04347826086956 ÷ 34 ≈ 2.150960475808819

Therefore, (−2)×(15)÷(23)×(−56)÷(34) ≈ 2.150960475808819.
Use the properties of operations and rules for multiplying and dividing to solve:

(−2)×(1/5)÷(2/3)×(−5/6)÷(3/4)
To solve the expression (−2)×(1/5)÷(2/3)×(−5/6)÷(3/4), we can follow the order of operations:

Step 1: Multiply -2 and 1/5
(-2) × (1/5) = -2/5

Step 2: Divide -2/5 by 2/3
(-2/5) ÷ (2/3) = (-2/5) × (3/2) = -6/10 = -3/5

Step 3: Multiply -3/5 by -5/6
(-3/5) × (-5/6) = (3/5) × (5/6) = 15/30 = 1/2

Step 4: Divide 1/2 by 3/4
(1/2) ÷ (3/4) = (1/2) × (4/3) = 4/6 = 2/3

Therefore, the solution for (−2)×(1/5)÷(2/3)×(−5/6)÷(3/4) is 2/3.
(9)÷(5/4)×(7/9)×(−5)÷(7/2)
To solve the expression (9)÷(5/4)×(7/9)×(−5)÷(7/2), we can follow the order of operations:

Step 1: Divide 9 by 5/4
9 ÷ (5/4) = 9 * (4/5) = 36/5

Step 2: Multiply (36/5) by (7/9)
(36/5) * (7/9) = (36 * 7) / (5 * 9) = 252/45 = 28/5

Step 3: Multiply (28/5) by (-5)
(28/5) * (-5) = -140/5 = -28

Step 4: Divide -28 by 7/2
-28 ÷ (7/2) = -28 * (2/7) = -56/7 = -8

Therefore, the solution for (9)÷(5/4)×(7/9)×(−5)÷(7/2) is -8.